A dictionary of euphemisms - Holder, R. W. (Oxford University Press, 1995)
There's an art to not saying what you mean, and A Dictionary Of Euphemisms investigates our all too common tendency to prefer vague or roundabout expressions to words which are blunt, precise, and often disagreeably true. Whey else do we say 'bijou', 'house of ill repute', and 'corporate entertainment', when what we really mean 'inconveniently small', 'brothel', and 'bribery'? Let A Dictionary of Euphemisms be your guide to the language of prudery, evasion, and deceit. Filled with thousands of quotations, definitions, derivations, and historical explanations, this dictionary offers compulsive browsing combined with essential reference.